If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a = h(b + c) * solve(b) Reorder the terms for easier multiplication: a = h * elosv * b(b + c) Multiply h * elosv a = ehlosv * b(b + c) Multiply ehlosv * b a = behlosv(b + c) a = (b * behlosv + c * behlosv) Reorder the terms: a = (bcehlosv + b2ehlosv) a = (bcehlosv + b2ehlosv) Solving a = bcehlosv + b2ehlosv Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Simplifying a = bcehlosv + b2ehlosv
| 2x+5(x-1)= | | 3(-11)[5(-3)-7(-2)]= | | 6xrqw+13xrqw=133 | | 9s-36=5s | | 64g^3-125h^3=0 | | 13(x-4)=8x-32 | | 16t^2=-h+100 | | 3/4+1/4x=3/4x-1/4 | | -4=3n-7n | | 2x-60=x | | x-2=14*2 | | 16t^2+h=100 | | 1-11-3x=32 | | x+by=c*x | | (2m-7)squared= | | 2(7)-2x=6 | | 12x-4(3x)=0 | | 4b-8b^2=0 | | x/2-1/5=x/3+1/4 | | Y+5/8=-2 | | -17x=391 | | 7y-18=-46+3y | | 6(1)-10x=77 | | 2x-5(x-2)=-6+3x-20 | | -6(8+5n)-5=6n+19 | | (8xy-y)(8xy-y)= | | 7y-10(6y-13)=77 | | 4x-24=-30+6x | | 11x+3=5x+27 | | -8=2n+2n | | 2y+7-22y= | | -7.97(-5+a)=56.586 |